Analysis of Land Use for Tourism Development in Bayat District, Klaten Regency - Mardika R, Richa; Taryono, Taryono (International Journal for Disaster and Development Interface, 2023)
The choice of research location in Bayat District is due to the use of land for tourism development inBayat District, Klaten Regency. This district stores various tourist attractions that are highlyrecommended to visit, besides being known for its pottery, batik, and Angkringan crafts, it turns outthat Bayat District also has tourist attractions that are no less interesting, especially Rowo Jomborand Sidoguro Hill, usually known as Tourist Hill, which is one of the most popular tourist attractionsin the area. a must-visit destination when visiting Klaten. One of the important assets owned by thelocal government of Klaten Regency which is the basis for regional economic growth is tourism. Withthe number of tourist areas, the welfare of the community has increased because there are manybusiness areas around the tourism area. But since the coronavirus as it is currently the tourism sectoris experiencing a collapse due to the impact of covid-19 and the implementation of PPKM, butcurrently the government is revitalizing the tourism sector so that unemployment does not increase.Bayat District is part of the Klaten Regency area which has a lot of potential both in terms of itsnatural conditions and the diverse social conditions of its people. This study aims to analyze thetourism factors in Bayat District and to know the evaluation of tourism development in Rowo Jomborand Sidoguro Hill. The method used is using qualitative methods, for data collection itself thisresearch uses primary and secondary data obtained by direct and indirect observations. The results ofthis study indicate that the availability of facilities and infrastructure is quite good, there is acomparison of visitors from year to year, and the mapping of the Rowo Jombor and Sidoguro Hilltourist areas in Krakitan Village and the results of the development evaluation show that there is anincrease in both physical and social factors.